COGNITIVISM AND ITS IMPLICATION IN THE SECOND LANGUAGE LEARNING - Suharno Suharno (Master Program in Linguistics, Diponegoro University, 2010)
This paper aims to elaborate cognitivism and its implications to the second language learning. Cognitive theory or approach views the learner as a thinking being and an active processor of information. Thus, learning is a process in which the learner actively tries to analyze the situations where the application of the rule would be appropriate and to make sense of data. In other words, we learn by thinking about and trying to make sense of what we see, hear and feel. In order to get a clear picture of the cognitive theory in relation to second language learning, other related theories were also described briefly from the historical points of view. In general cognitivism can be grouped under the innatist model which is also known as ‘nativist’. ‘mentalism’ (thinking as rule-governed activity), ‘rationalism’. The implications of cognitive theories can be revealed in the basic teaching techniques which cover activities such as problem-based solving activity, discovery learning, cognitive strategies, project-based learning, etc.